Geotechnical Evaluation of Limestones from Cape Monze and Adjoining Areas, Karachi, Pakistan for Their Utilization as Road Aggregate: Geotechnical Evaluation of Limestones from Cape Monze and Adjoining Areas, Karachi, Pakistan for Their Utilization as Road Aggregate - Bilal, Mohammad; Khan, Adnan (International Journal of Economic and Environmental Geology, 2019)
Limestone samples (n = 19) were collected from outcrops of Nari and Gaj formations for the determination of physicochemical and mechanical characteristics. Compressive strength of Nari and Gaj formations varied in the range of 29-63 and 94-32 MPA with mean of 44 and 58 MPA respectively. Density of Gaj Formation (range: 2364-3264; mean: 2893 Kg/m3) is relatively higher than Nari Formation (range: 2321-3284; mean: 2565 Kg/m3). Mean specific gravity of both Nari and Gaj formations is 2.5. Absorption of Nari Formation (mean: 2.64) is higher than the Gaj Formation (mean: 1.78). Mean Sulphate soundness of Nari Formation (8.7%) is slightly higher than Gaj Formation (8.5%). Abrasion values of both formations are within the AASHTO reference range (< 40%) where mean value of Loss Angles for Nari Formation is 34% and Gaj Formation is 26%. Crushing values of both Nari (10-50%) and Gaj (10-25%) formations where mean of Nari (27%) is double the mean of Gaj (13%) Formation. Mean water-soluble sulphate and chloride of both formations is same (0.1% and 0.04% respectively). Both formations have alkaline pH (8.1±). Mean TOC content of Nari and Gaj formations is 0.4%. Carbonate% of Nari and Gaj formations is < 46%. Clay lumps and friable particles in both formations are highly variable but the mean values are within permissible range (< 1%). Elongation Index of both formations is double (30) the standard EI value (15%) set by National Highway Authority, Pakistan. Mean Flakiness value of both formations is 20%.